Method For Producing Peptide Fractions And Use Thereof; Offenlegungsschrift - Danneel, Hans-Jürgen
The invention relates to a method for producing enriched peptide fractions from protein-containing raw materials, in which protein hydrolysates are separated using chromatography, according to the physiochemical properties thereof, by means of stationary phases with an aqueous solution as an elution agent.